STUDY OF COGNITIVE PROCESSES OF ONCOLOGICAL PATIENTS - Allaberganova Gozal Adilbek qizi (American Journals Publishing, 2024)
Today, oncological diseases have an increasing trend all over the world. Early detection of the development of oncological disease, use of effective methods of treatment, extension of the remission period, and development and improvement of rehabilitation measures constitutes the content of fighting the disease. In the treatment of a patient diagnosed with cancer, it is important not only to use medical measures, but also to take into account the patient's psychology. From this point of view, monitoring the psychological state of oncology patients and having a positive psychological effect on them serves to increase the effectiveness of medical procedures, which are the main type of treatment.The article recognizes how important it is to study the cognitive processes of oncology patients and the specific features of conducting psychodiagnostics.
Keywords: Oncology, psychodiagnostics, patients, healthy people, disease